2018
DOI: 10.1111/and.13065
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of apple vinegar on reproductive parameters in male rat model of nonalcoholic fatty liver disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is associated with low testosterone levels in serum. The aim of this study was to evaluate the effect of apple vinegar on fertility indices in a rat model of NAFLD. To study this effect, 32 adult male rats were divided into four groups: A-normal diet, B-high-fat diet (HFD), C-apple vinegar and D-HFD plus apple vinegar. At the end of the week 22, the Lee index, serum lipid profiles, liver enzymes, glucose and total antioxidant levels (TAC) in serum were determined. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
(57 reference statements)
0
4
2
Order By: Relevance
“…Unlike our result, a number of studies showed a high level of sperm abnormal morphology in diabetes, as compared to the control group (Ghorbanlou et al, 2020; Mohammadghasemi et al, 2018). In addition, Tsao et al (2015) demonstrated negative significant correlation between sperm morphology and concentration with body adiposity in a 7630 male population (Tsao et al, 2015).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike our result, a number of studies showed a high level of sperm abnormal morphology in diabetes, as compared to the control group (Ghorbanlou et al, 2020; Mohammadghasemi et al, 2018). In addition, Tsao et al (2015) demonstrated negative significant correlation between sperm morphology and concentration with body adiposity in a 7630 male population (Tsao et al, 2015).…”
Section: Discussioncontrasting
confidence: 99%
“…It is also of note that aforementioned anomalies are reported to be higher in the prediabetic state as compared to the diabetic state, based on the fact that in the diabetic state, an adaptation is achieved and animal or individuals has been able to partially overcome the inflammatory stage unlike in pre-diabetic state (Akbarian et al, 2021;Nevin et al, 2018;Portela et al, 2015). Unlike our result, a number of studies showed a high level of sperm abnormal morphology in diabetes, as compared to the control group (Ghorbanlou et al, 2020;Mohammadghasemi et al, 2018). In addition, Tsao et al (2015) demonstrated negative significant correlation between sperm morphology and concentration with body adiposity in a 7630 male population (Tsao et al, 2015).…”
Section: Discussioncontrasting
confidence: 63%
“…Steatosis was considered moderate if it was in the range of 33% to 66%. Finally, if it exceeded 66%, it was called severe [ 16 ]. Inflammatory cells were counted in representative lobules and expressed as a percentage for histological investigation of the liver.…”
Section: Methodsmentioning
confidence: 99%
“…Apple vinegar also improves spermatogenesis testicular function by reducing HOMA-IR, Lee index, apoptosis of germ cells, and increasing total antioxidants in a rat model of NAFLD [ 16 ]. Little is known about NAFLD and female reproductive function.…”
Section: Introductionmentioning
confidence: 99%
“…The Homeostatic Model of Assessing Insulin Resistance (HOMA-IR) was determined based on the flowing formula: HOMA-IR=Insulin×Glucose/22.5 [20].…”
Section: The Homeostatic Model Of Assessing Insulin Resistancementioning
confidence: 99%